Creating Thinking Accountants: Focus on the Approaches in Teaching-learning of Accounting Practices - Vaidya, Shipra (JOURNAL OF INDIAN EDUCATION, 2008)
Is teaching of Accounting confined only to reading the financial data and its presentation in a required structured format? Many people in today’s society think of an accountant as simply a glorified book keeper and a steward who manages the financial affairs of other persons. But, the role of an accountant has now shifted from that of a mere recorder of transactions to that of the member providing relevant information to the decision-making team. Accountants today are working in existing new growth areas such as forensic accounting, budget accounting, environmental accounting, e-commerce and the various agencies within the public sector. The advent of information technology have resulted in the development of necessary skills for today’s accountant which include the ability to develop persuasion and communication skills; analytical skills; willingness to embrace change and assume risk and develop competence in computer technology. But a question that raises its head from time to time is ‘Are we really preparing our students to face the challenges in business operations for the 21st century’? The accounting students are widely criticised for their inflexibility in problemsolving and insufficient communication skills. There are several pedagogies recommended by commerce educators to improve the effectiveness in delivering the accounting curriculum. This paper attempts to contextualise the teaching methodologies in order to make transaction of accounting curriculum purposeful, meaningful and interesting at the school level.